447 A Study of Influence of Relationship on Life Style and Mental Health of Adolescent. (October 2012) - Sharma, M
Abstract : Adolescent period when teen having impact of broken relationship, which affects teens ability to function in life. Aims & objectives: To study influence of relationship and explore possible causes and solutions to this problem To highlight the importance of impact of relationship on life style and mental health of teens. Material and method: Study done in two Private coaching institute. 250 children of age group 15 to 20 years from two renowned institutes with their parents were interviewed with the help of a pre-set questionnaire. The questions were aimed at knowing the life style and impact of relationship on these children. From this information various problems in each child were identified and then analyzed. Observations: Total number of children was 250, 140 were girls and rest 110 boys. age from 15 to 20 years. 30% of joint family, 45% nuclear family and 25%, 10% broken home Impact on mental health 50%, Social withdrawal 25% Refusal to go to school 25%Poor study behavior and skills 10%, disruptive behavior in classroom 12%, school performance dropping 30%, emotionally unstable behavior 10%, 20% Poor hygiene and grooming 15% Involved in reckless activities 15% Using alcohol or other drugs 10% Skipping school 10% violent behavior. Conclusion: The study clearly bring out that, there is strong influence & impact on the mental health and social development and life style of children Broken relationship having strong impact on mental health, this can be controlled timely by parents with trust and open communication and adolescent counseling.